Conceptualisation of Accounting Communication through the Lens of Deontology, Ontology and Epistemology - Ngwakwe, Collins, C (Acta Universitatis Danubius. Communicatio, 2024)
Accounting as an information system is somewhat exclusive from other genre of communication systems; it conjures legitimacy through the accountants’ claim of objectivity. This paper inclines on the philosophical theories of deontology, ontology, and epistemology to deconstruct accounting communication. The objective of the paper is to provide a critical conceptualisation of accounting communication from the lens of deontology, ontology, and epistemology and to propose a framework for further research and to guide the communication of accounting information. The approach is a critical and intuitive Hermeneutical deconstruction of philosophical texts on deontology, entomology, and epistemology to provide a mirror of accounting communication. Findings show a criticism from critical scholars, which decries accountants’ claim of objectivity in accounting communication as rather partial given the one-sided construction of reality. The paper is thus significant with a critical discussion of accounting communication, which bridges a gap in the literature. It provides academic and practical significance for improving accounting theory and discourse in higher education and for accounting practice. The paper adds novel value and contributes to the philosophy of accounting communication with the development of a framework for accounting communication which integrates deontology, ontology, and epistemology of accounting.